Penerapan Model Pembelajaran Berbasis Projek untuk Meningkatkan Kemampuan Berpikir Kreatif pada Materi Enzim - Darmansah, Dani (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The ability to think creatively is very much needed for the next generation of this nation to face global challenges in the future. The increase in technology and the explosion of the population, which is accompanied by a lack of supplies of natural resources, greatly demands the ability to adapt creatively and the ability to find imaginative solutions. The same picture appears in the world of education. The emphasis is more on rote thinking, looking for one correct answer to the questions given. Higher thought processes, including creative thinking, are rarely trained. Attention and research on individual creativity is rarely carried out in schools. To overcome this, the authors apply a learning model, namely Project-Based Learning to improve students' creative thinking skills on enzyme material. This model has characteristics, namely the existence of problems or challenges, determining solutions, collaborative problem solving, making the learning experience more interesting and fun, allowing students to express many ideas, build work skills, and can produce real products. Good il. Based on the results of research conducted at the school where the author works, namely SMA Negeri I Karangnunggal, Tasikmalaya Regency, Class XII IPA 5 students, it turns out that the results are quite good. The students' creative thinking ability, especially on the indicators of fluent thinking, flexible thinking and original thinking showed a fairly good increase. The ability to think in detail and to think in judgment has improved, but needs to be retrained to be even better. Student responses regarding the learning model gave a good response, especially regarding fun learning, but the weakness is that it is less time effective and requires money to make products